Pengaruh Substitusi Tepung Pisang Tongka Langit Pregelatinisasi Terhadap Sifat Fisikokimia Cookies - Picauly, Priscilia; Lawalata, Vita N; Nahatue, Maimuna (Universitas Pattimura, 2025)
This study aimed to analyze the functional properties of pregelatinized tongka langit banana flour (TPTLP) at different maturity levels and to determine the effect of substituting TPTLP on the physicochemical properties of cookies at the optimal maturity level. This study was designed using a completely randomized design consisting of one factor, with substitution treatments of wheat flour (TT) and TPTLP, consisting of 0%: 100%, 25%: 75%, 50%: 50%, 75%: 25%, and 100%: 0% with two replications. The parameters analyzed included the water absorption capacity, vitamin A content, and antioxidant activity of TPTLP, as well as the moisture content, ash content, protein content, fat content, crude fiber, carbohydrates, breaking strength, and crispness of the cookies. The results showed that tongka langit bananas at maturity level II exhibited better functional properties than those at level I. Furthermore, substitution with TPTLP (100%, 75%, 50%, 25%, and 0%) from maturity level II significantly affected the physicochemical properties of cookies. Increasing levels of TPTLP substitution led to higher moisture, ash, and crude fiber contents, while protein content, breaking strength, and crispness decreased.